Administrative – Territorial Reform in Ukraine: Implementation Challenges and Control Mechanism Improvement - SHAPOVAL, Roman Vladimirovich; VITS’KO, Elena Viktorovna; DEMENKO, Olga Ivanovna; SOLNTSEVA, Kristina Vladimirovna (Journal of Advanced Research in Law and Economics, 2016)
The article deals with the possible directions of the administrative-territorial reform in Ukraine in present conditions. The main objective of the study is to develop practical recommendations for carrying out an administrative-territorial reform in Ukraine based on the experience of Western European countries. In this paper the authors applied the method of legal modeling, the prognostic method, which enabled to give scientifically based forecasts on the prospects of the administrative-territorial reform in Ukraine and the implementation of efficient administrative and territorial management. Scientific novelty of the paper includes outlining the essence of the administrative and territorial reform in modern Ukraine, complex and hierarchical national conditions and reform factors. The article also states the necessity of broad decentralization and deconcentration of power, which would enable to stabilize the social situation in the country and to promote the democracy. The undertaken analysis allowed identifying a new form of government, which cannot be considered either unitary or federal. This form of government can be found in Western European countries and is characterized by the indivisibility of the state, which acknowledges local autonomies and implies the most extensive administrative decentralization. The authors propose to improve Ukraine’s control mechanisms according to this form of state structure and taking into account the status of the regions. The article makes a distinction between the concepts ‘the territorial structure of the state’ and ‘the administrative-territorial structure of the state’, the original author’s definitions provided. Practical conclusions and recommendations on carrying out the administrative-territorial reform in Ukraine and proposals for optimization of the control mechanism can be used by Western European countries facing administrative and territorial challenges.
Keywords: Administrative-Territorial Reform; Regional Links; Control Mechanism Improvement; Unitary State; Federal Government; Region; District